The Central Nervous System Contains ILC1s That Differ From NK Cells in the Response to Inflammation - Romero-Suárez, Silvina; Del Rio Serrato, Alba; Bueno, Roemel Jeusep; Brunotte-Strecker, Daniel; Stehle, Christina; Figueiredo, Caio Andreeta; Hertwig, Laura; Dunay, Ildiko R.; Romagnani, Chiara; Infante-Duarte, Carmen (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) are tissue resident cells with organ-specific properties. Here, we show that the central nervous system (CNS) encompasses ILCs. In particular, CD3-NK1.1+ cells present in the murine CNS comprise natural killer (NK) cells, ILC1s, intermediate ILC1s (intILC1s) and ex-ILC3s. We investigated the properties of CNS-ILC1s in comparison with CNS-NK cells during steady state and experimental autoimmune encephalomyelitis (EAE). ILC1s characteristically express CXCR3, CXCR6, DNAM-1, TRAIL and CD200R and display heightened TNF-α production upon stimulation. In addition, ILC1s express perforin and are able to degranulate, although in a lesser extent than NK cells. Within the CNS compartments, ILC1s are enriched in the choroid plexus where very few NK cells are present, and also reside in the brain parenchyma and meninges. During EAE, ILC1s maintain stable IFN-γ and TNF-α levels while in NK cells the production of these cytokines increases as EAE progresses. Moreover, the amount of ILC1s and intILC1s increase in the parenchyma during EAE, but in contrast to NK cells, they show no signs of local proliferation. The upregulation in the inflamed brain of chemokines involved in ILC1 migration such as CXCL9, CXCL10 and CXCL16 may lead to a recruitment of ILC1s from meninges or choroid plexus into the brain parenchyma. In sum, CNS-ILC1 phenotype, distribution and moderate inflammatory response during EAE suggest that they may act as gatekeepers involved in the control of neuroinflammation.